A catalyst-free rapid, practical and general synthesis of 2-substituted quinazolin-4(3H)-ones leading to luotonin B and E, bouchardatine and 8-norrutaecarpine1. Issue 76 (19th August 2015) - Rao, K. Raghavendra; Mekala, Ramamohan; Raghunadh, Akula; Meruva, Suresh Babu; Kumar, S. Praveen; Kalita, Dipak; Laxminarayana, Eppakayala; Prasad, Bagineni; Pal, Manojit
<x xml:space="preserve">Abstract</x> Formamide has been identified as an ammonia surrogate in the construction of quinazolin-4(3H)-one ring leading to several alkaloids.